2018
DOI: 10.1016/j.actbio.2018.01.011
|View full text |Cite|
|
Sign up to set email alerts
|

Short peptide analogs as alternatives to collagen in pro-regenerative corneal implants

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
4
40
0
1
Order By: Relevance
“…In that respect, a 36 amino-acid long CMP chain (O'Leary et al, 2011) was modified by addition of a two-amino acid linker (Islam et al, 2016), covalently conjugated to a backbone of mechanically tougher polyethylene glycol (PEG), and subsequently crosslinked (Rubert Pérez et al, 2015). The resulting CMP-PEG stabilised hydrogels were as effective as full-length collagen gels in promoting corneal functional repair as recently shown in mini-pigs (Jangamreddy et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In that respect, a 36 amino-acid long CMP chain (O'Leary et al, 2011) was modified by addition of a two-amino acid linker (Islam et al, 2016), covalently conjugated to a backbone of mechanically tougher polyethylene glycol (PEG), and subsequently crosslinked (Rubert Pérez et al, 2015). The resulting CMP-PEG stabilised hydrogels were as effective as full-length collagen gels in promoting corneal functional repair as recently shown in mini-pigs (Jangamreddy et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…In contrast, full thickness implants, where the integrity of host endothelium is compromised, depend upon minimising the wound healing response and development of opaque scar tissue (retro‐corneal membrane [RCM] formation) to retain transparency. Accordingly, lamellar implants have enjoyed some degree of success (P. Fagerholm et al, ; Islam et al, ; Jangamreddy et al, ), whereas full thickness implants do not remain clear due to RCM formation in many cases (Hicks & Hamilton, ; Obata & Tsuru, ; Rajendran, Netuková, Griffith, Forrester, & Kuffová, ; Yum, Kim, & Kim, ). However, they can function as tectonic grafts allowing preservation of the eye in the case of a nonhealing wound and later replacement with a full thickness, endothelium‐intact, penetrating allograft.…”
Section: Introductionmentioning
confidence: 99%
“…ALK was used to implant the hydrogels into minipig eyes and the transplanted corneas were followed up for 12 months. Implanted corneas remained clear and both epithelium and stroma regenerated successfully [204].…”
Section: Hydrogel-based Scaffoldsmentioning
confidence: 89%
“…To address this, new biomaterials, such as collagen gels, synthetic polymers, and tissue-engineered scaffolds, have been developed to repair, regenerate, or replace the damaged cornea [82]. Jangamreddy et al found that one kind of peptide analogs as alternatives to collagen promoted regeneration of corneal tissue by stimulating in-growing corneal epithelium cells to secrete EVs for generating matrix components [55]. During corneal wound healing, mouse corneal epithelial cell-derived exosomes induced fibroblast proliferation and transformation of keratocytes to myofibroblasts, mediating intercellular communication between the corneal epithelium and stroma [56].…”
Section: Corneal Allograft Rejectionmentioning
confidence: 99%